Serotonin: A Potent Immune Cell Modulator in Autoimmune Diseases - Wan, Minjie; Ding, Lili; Wang, Dong; Han, Jiawen; Gao, Pujun (Frontiers in Immunology, 2020)
Serotonin, also known as 5-hydroxytryptamine (5-HT) is a signaling mediator that regulates emotion, behavior, and cognition. Previous studies have focused more on the roles of 5-HT in the central nervous system (CNS). However, 5-HT also shares a strong relationship with the pathological cases of tumor, inflammation, and pathogen infection. 5-HT participates in tumor cell migration, metastatic dissemination, and angiogenesis. In addition, 5-HT affects immune regulation via different 5-HT receptors (5-HTRs) expressed immune cells, including both innate and adaptive immune system. Recently, drugs targeting at 5-HT signaling were tested to be beneficial in mouse models and clinical trials of multiple sclerosis (MS) and inflammatory bowel disease (IBD). Thus, it is reasonable to assume that 5-HT participates in the pathogenesis of autoimmune diseases. However, the underlying mechanism by 5-HT modulates the development of autoimmune diseases has not been fully understood. Based on our previous studies and pertinent literature, we provide circumstantial evidence for an essential role of 5-HT, especially the regulation of 5-HT on immune cells in the pathogenesis of autoimmune diseases, which may provide a new point cut for the treatment of autoimmune diseases.